Prevalence and characteristics of acid gastro-oesophageal reflux disease in Jackhammer oesophagus. Issue 10 (October 2016) - Mallet, Anne-Laure; Ropert, Alain; Bouguen, Guillaume; Siproudhis, Laurent; Boutroux, Dominique; Bretagne, Jean-François; Brochard, Charlène
Abstract: Background: An association between acid gastro-oesophageal reflux disease (GERD) and Jackhammer oesophagus has been suggested. Aim: To assess the prevalence and characteristics of acid-GERD in Jackhammer oesophagus and the efficacy of proton pump inhibitors. Methods: Data and outcomes of patients with Jackhammer oesophagus were assessed. Two groups were compared: (i) GERD, defined by endoscopic oesophagitis or by an increase in acid exposure time or by an acid-hypersensitive oesophagus and (ii) non-GERD defined by normal oesophageal acid exposure without acid-hypersensitive oesophagus. Results: Among the 1994 high-resolution manometries performed, 44 Jackhammer oesophagus (2.2%) were included (sex ratio M/F: 19/25; median age: 66 [61–75] years). Nineteen patients (43.2%) had GERD, 16 (36.4%) had no GERD and 9 patients (20.4%) were undetermined. Dysphagia was the predominant symptom (37/43 (86%)). After a median follow-up of 25.3 months [9.6–31.4], dysphagia was improved in 22/36 (61.1%) patients. Dysphagia improvement as well as other symptoms improvement was not associated with GERD status or proton-pump inhibitors use. Conclusion: The prevalence of GERD is high among patients with Jackhammer oesophagus. The rates of symptom improvement in Jackhammer oesophagus were high regardless of the use of proton-pump inhibitors treatment or of the presence of GERD.